Evaluating environmental sustainability and ecosystem disruption caused by construction demolition waste in a university precinct: a case study from Malang, Southeast Asia - Sugiharto, Ketut; Marjono , Marjono; Ciptadi, Gatot; Wisnumurti, Wisnumurti (Eastern-European Journal of Enterprise Technologies, 2025)
This research focuses on evaluating the ecological potential of reusing construction and demolition waste (CDW) from brick wall debris in Malang City, East Java, Indonesia, as a sustainable substitute for natural fine aggregate in construction. The problem addressed is the increasing volume of CDW driven by rapid urban growth, especially in student-dominated districts, which poses environmental risks through landfill overuse, and soil degradation. The study employs field surveys, structured interviews, SEM-EDX analysis, and gradation testing to assess the physical and chemical suitability of recycled CDW. The results demonstrate that brick-based CDW exhibits stable particle gradation, an acceptable fineness modulus, with approximately 12.71% of the material passing through the 0.075 mm sieve, and contains no hazardous levels of leachable chemicals, making it suitable for reuse as a construction sand substitute. These findings are explained by the inherent mineral stability of fired clay bricks and the controlled processing methods used, which reduce impurities and optimize particle distribution. A distinctive feature of the results is the integration of chemical safety verification via SEM-EDX with practical gradation analysis, ensuring both environmental safety and material performance in a single evaluation framework. The results can be practically applied in the manufacture of urban construction materials under conditions where local CDW. Implementation is most effective in medium-sized cities with high construction activity and limited natural sand resources, particularly where municipal waste management systems can support material sorting and processing. By applying these findings, urban areas can reduce environmental pressure from CDW, promote circular economy practices, and advance sustainable construction technology